FROM CONVENTIONAL READING TO MOODLE-BASED LEARNING: AN EXPERIMENTAL STUDY ON UNDERGRADUATE STUDENTS’ READING COMPREHENSION - Hidayati, Hidayati; Indrawati, Inda; Sudaryati, Sri; Abrar, Andi Muhammad; Rusdin, Diyenti; Marzuki, Marzuki (LEMBAGA PENELITIAN DAN PENGABDIAN PADA MASYARAKAT, 2025)
The rapid advancement of digital technology has encouraged the integration of Learning Management Systems (LMS) in higher education, including in reading instruction. Although Moodle is widely adopted, empirical evidence based on experimental approaches that directly examine its effectiveness in enhancing undergraduate students’ reading comprehension remains limited, particularly in comparison with conventional reading instruction. This study aimed to investigate the effect of Moodle-based reading instruction on students’ reading comprehension and to compare learning outcomes between students taught through Moodle and those taught through traditional instructional methods. A quasi-experimental research design employing a pretest–posttest control group was applied. The participants consisted of 46 undergraduate students divided into two intact classes: an experimental group (n = 23) and a control group (n = 23). The experimental group received reading instruction through Moodle, integrating structured learning materials, interactive activities, and formative assessments, while the control group was taught using conventional face-to-face reading instruction with printed materials and teacher-led discussions. A reading comprehension test was administered as both a pretest and a posttest. Data were analyzed using descriptive statistics, paired-samples t-tests to examine within-group improvement, independent-samples t-tests to compare posttest performance between groups, and effect size analysis to assess practical significance. The results revealed that both groups demonstrated significant improvement in reading comprehension from pretest to posttest; however, the experimental group showed significantly greater gains than the control group. Furthermore, the posttest comparison indicated a statistically significant difference with a large effect size, suggesting that Moodle-based instruction had a substantial and educationally meaningful impact on students’ reading comprehension. Overall, the findings indicate that Moodle-based reading instruction is an effective approach for enhancing undergraduate students’ reading comprehension and offers considerable pedagogical benefits for reading instruction in higher education contexts.